DIFFERENCES IN THE AMOUNT OF POLYPHENOLIC COMPOUNDS IN DIFFERENT AERIAL PARTS OF PLANTAGO MAJOR - Zubair, M.; Lindholm, Nybom Rumpunen (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The common weed Plantago major (common plantain) has been used as a wound healing remedy in almost all parts of the world. It has also been used in the treatment of a number of other diseases in folk medicine. The biological activities of P. major leaves are wound healing, anti-inflammatory, analgesic, antioxidant, weakly antibiotic, immuno-modulating and anti-ulcerogenic properties. Polyphenols and polysacharides in the leaves could possibly act synergistically to stimulate wound healing. The aim of the present study is to determine which of the aerial plant parts are most useful for production of specific phenolic compounds. Seed-propagated P. major plants were grown in a greenhouse. Leaves (both fresh and old), flowering stalks and seeds were harvested from five different populations obtained by one generation of controlled selfing (15 leaves per population, 15 flowering stalks and seeds from 15 spikes) and were freeze-dried. Leaves, flowering stalks and seeds were then ground and extracted with a 50% ethanol solution in an ultrasonic bath for 15 minutes. These extracts were analyzed using HPLC to quantify different phenolic compounds. The amount of some phenolic compounds (e.g. plantamajoside) in P. major decreases from young leaves to seed (young leaves - old leaves - flowering stalks - seeds), whereas other compounds (e.g. verbascoside) increase from young leaves to seeds (young leaves - flowering stalks and seeds). The maximum amount of plantamajoside was thus obtained in samples of young leaves while maximum content of verbascoside was obtained in flowering stalks and seeds (no significant difference between these).